PSVIII-39 Genome-wide DNA methylation alteration in prenatally stressed Brahman heifer calves with the advancement of age. (5th December 2019) - Cilkiz, Kubra Z; Baker, Emilie C; Riggs, Penny K; Randel, Ronald D; Riley, David G; Welsh, Thomas
Abstract: This study investigated whether DNA methylation patterns changed over the first five yr of life within prenatally stressed (PNS) heifer calves compared to change within a Control group. Prenatal stress was induced by the transportation of pregnant Brahman cows for 2-hr periods at 60±5, 80± 5, 100±5, 120±5, and140±5d of gestation. White blood cells were sampled from the same 6 PNS heifer calves and 8 Control heifer calves at 28 d and 5 yr of age. The DNA methylation data were generated through Reduced Representation Bisulfite Sequencing. Based on results of mapping and bioinformatics analyses, 73, 758 hypermethylated and 73, 367 hypomethylated CpG sites, 375 hypermethylated and 377 hypomethylated CHG sites, 735 hypermethylated and 842 hypomethylated CHH (C = cytosine; G = guanine; H = either adenine, thymine, or cytosine) sites were obtained from 28-d-old PNS calves compared to when they had matured into 5-yr-old PNS cows (P ≤ 0.05). The 28-d-old Control heifer calves contained 53, 005 hypermethylated and 57, 103 hypomethylated CpG sites, 200 hypermethylated and 202 hypomethylated CHG sites, 439 hypermethylated and 535 hypomethylated CHH sites compared to when they matured into 5-yr-old Control cows (P ≤ 0.05). As DNA methylation of gene promoter regions is associated with reduced transcription activity, strongly hypermethylated and hypomethylated CpG sites located in promoter regions underwent Ingenuity Pathway Analysis. The top canonical pathways altered by strongly hypermethylated and hypomethylated CpG sites between 28-d-old and 5-yr-old PNS cows were 4-1BB Signaling in T Lymphocytes (P = 0.00169) and Transcriptional Regulatory Network in Embryonic Stem Cells (P = 0.000744). Mineralocorticoid Biosynthesis (P = 0.00901) and Transcriptional Regulatory Network in Embryonic Stem Cells (P = 0.000804) were the other top canonical pathways altered between 28-d-old and 5-yr-old Control cows. PNS calves appeared to develop an altered epigenome compared to Control group calves during the first five yr from birth.